Raja of Narayan: A colonised tiger or a nation? - Reyhan Özer Tanıyan (Literacy Trek, 2020)
Known best for his novels set in fictional town of Malgudi, R. K. Narayan, as a novelist of the colonized land, India, was affected by the culture of the colonial power. Narayan was also aware that the imposition of English education over an inferior society is a vital part of the colonial way of redesigning the colonized culture. Thus, he used the English, the language of the colonist, and literary forms to scrutinize colonialism and to illustrate the colonization process of the Indian society continually and gradually under erosion within colonial rule. He penned a synthesis between the Indian elements and the colonial ones in his novels, especially in Malgudi series. In A Tiger of Malgudi, R. K. Narayan creates an intriguing animal allegory within an innovative style of plot construction and characterization, which makes this novel distinctive in the series. In the novel, the fable-like narration is mingled with Hindu philosophy such as karma and reincarnation in order to draw attention to rich Indian heritage and Hinduism that are under the threat of degeneration by colonial culture. As a first person story-teller, the tiger Raja, narrates his life-story, shares his feelings and thoughts for human beings and reconsiders the events he has experienced. His narration bears the implications of a critique of colonial power and Hindu spirituality as well. Thus, in this article, the focus will be on the narration of the tiger which is a synthesis of colonial and Indian elements within the concepts of postcolonial theories; displacement, identity and power, and Hindu philosophy; karma, reincarnation, samsara and samādhi.